Calculo químicocuántico del cambio de acidez de varias zeolitas ZSM5 causado por un dopante - Torres Pérez, Eddy Giovanny (2018)
Abstract:The acid H-ZSM zeolite is of great importance for the wide number of industrial processes that use it as a catalyst. This theoretical work, based on experimental results, studies the formation of Brönsted acid sites in zeolite H-ZSM5 doped with different metals, specifically Al, Ga and B, in different Si/T ratios (where T symbolises the doping metal). The theoretical optimization results were obtained utilizing the VASP software and were compared with the experimental characterization of programed temperature ammonia thermodesorption (TPD). According to the structural results, the greater is the number of substituted silicon atoms with other metals in the aluminosilicates, the greater is the distance of the O-H bond in the Brönsted acid sites, showing less acid strength. However, for the galiumsilicates and borosilicates, this is an inverse trend: the distances of the O-H bond increase as the number of substituted Si atoms decreases. The formation energy of the Brönsted bond in aluminosilicates was the greatest, followed by the galiumsilicates and borosilicates, when the relation of Si / T is similar, coinciding with the experimental results.